Musical communication - Miell, Dorothy; Macdonald, Raymond; Hargreaves, David J. (New York Oxford university press, 2005)
The first book to examine how music can act as a form of communication, presenting a broad interdisciplinary perspective - including biological, cultural, social, and cognitive processesFrom the same editors who produced the successful and highly praised 'Musical Identities'A new addition to the prestigious Oxford University Press music psychology list, the only such list aroundMusic is a powerful means of communication. It provides a means by which people can share emotions, intentions, and meanings even though their spoken languages may be mutually incomprehensible. It can also provide a vital lifeline to human interaction for those whose special needs make other means of communication difficult. Music can exert powerful physical effects, can produce deep and profound emotions within us, and can be used to generate infinitely subtle variations of expressiveness by skilled composers and performers.This new addition to the music psychology list brings together leading researchers from a variety of academic and applied backgrounds. It examines how music can be used to communicate and the biological, cognitive, social, and cultural processes which underlie such communication. Taking a broad, interdisciplinary look at all aspects of communication, from the symbolic aspects of musical notation, to the use of music in advertising, the book is the first of its kind. It will be valuable for all those involved in music psychology, music education, and communication studies.Readership: Music psychologists, music educators, music therapists, expermental psychologists